Understanding the Situational Antecedents of CEO Regulatory Focus - Lorenz Graf-Vlachy; François Neville; Cole Evan Short; Franz Xaver Völkl (Journal of Management Studies, 2024)
Despite the impact of CEO regulatory focus on a wide range of organizational outcomes, most research does not consider how regulatory focus can vary based on situational factors. Taking an interactionist perspective rooted in industrial-organizational psychology, we propose that CEO regulatory focus exhibits variance driven by situational factors, namely, a CEO's job demands. Integrating this perspective with regulatory focus theory and research on executive job demands, we theorize and test the extent to which CEO regulatory focus is influenced by relative firm performance, with stakeholder activism and CEO tenure as moderators of this relationship. Using a sample of large U.S. companies, our tests offer evidence for how situational factors cause CEO regulatory focus to vary. We conclude our work by developing a research agenda regarding situational antecedents of CEOs' intrapersonal constructs more broadly.
Keywords: 650; CEO; regulatory focus; executive job demands; tenure; stakeholder activism